The Effect of Ketogenic Diet on Inflammatory Arthritis and Cardiovascular Health in Rheumatic Conditions: A Mini Review - Ciaffi, Jacopo; Mitselman, Dmitri; Mancarella, Luana; Brusi, Veronica; Lisi, Lucia; Ruscitti, Piero; Cipriani, Paola; Meliconi, Riccardo; Giacomelli, Roberto; Borghi, Claudio; Ursini, Francesco (Frontiers in Medicine, 2021)
The principle of ketogenic diet (KD) is restriction of carbohydrates to a maximum of 5–10% of the total daily caloric intake, aiming at shifting body metabolism toward ketone bodies. Different studies suggested promising results of KD to help patients to lose weight, to reduce insulin requirements in diabetes, to supplement cancer protocols, to treat neurological conditions and to optimize control of metabolic and cardiovascular diseases. However, literature about the anti-inflammatory properties of KD in rheumatic diseases is still limited. The beneficial effects of weight loss in patients with inflammatory arthritis can be explained by biomechanical and biochemical factors. Obesity is associated with macrophage activation and production of pro-inflammatory cytokines including TNF-α, IL-1b, and IL-6. The clinical effect of KD may be primarily attributed to improvement of insulin sensitivity. Insulin resistance is associated with an increase of TNF-α, IL-1α, IL-1β, IL-6, and leptin. Moreover, reduction of body's adipose tissue and weight loss account for part of the anti-inflammatory effects and for the impact of KD on cardiovascular health. In rheumatoid arthritis, fasting was shown to be effective in reducing disease symptoms, possibly through the production of β-hydroxybutyrate (BHB), the main ketone body. BHB may exert inhibitory effects also on IL-17 and intermittent fasting improved the clinical manifestations of psoriatic arthritis. In ankylosing spondylitis, current literature doesn't allow to draw conclusion about the effects of KD. Future prospective studies will be needed to elucidate the potential beneficial effects of KD on specific domains and clinical outcomes in patients with inflammatory arthritis.